The educational impact of web-based and face-to-face patient deterioration simulation programs: An interventional trial. (May 2018) - Chung, Catherine; Cooper, Simon J.; Cant, Robyn P.; Connell, Cliff; McKay, Angela; Kinsman, Leigh; Gazula, Swapnali; Boyle, Jayne; Cameron, Amanda; Cash, Penny; Evans, Lisa; Kim, Jeong-Ah; et al.
Abstract: Background: There are international concerns relating to the management of patient deterioration. The "failure to rescue" literature identifies that nursing staff miss cues of deterioration and often fail to call for assistance. Simulation-based educational approaches may improve nurses' recognition and management of patient deterioration. Objectives: To investigate the educational impact of the First2Act web-based (WB) and face-to-face (F2F) simulation programs. Design & Setting: A mixed methods interventional cohort trial with nursing staff from four Australian hospitals. Participants: Nursing staff working in four public and private hospital medical wards in the State of Victoria. Methods: In 2016, ward nursing staff ( n = 74) from a public and private hospital completed three F2F laboratory-based team simulations with a patient actor in teams of three. 56 nursing staff from another public and private hospital individually completed a three-scenario WB simulation program (First2ActWeb) [A 91% participation rate]. Validated tools were used to measure knowledge (multi-choice questionnaire), competence (check-list of actions) and confidence (self-rated) before and after the intervention. Results: Both WB and F2F participants' knowledge, competence and confidence increased significantly after training ( p ≤0.001). Skill performance for the WB group increased significantly from 61% to 74% ( p ≤ 0.05) and correlated significantly with post-test knowledge ( p = 0.014). No change was seen in the F2F groups' performance scores. Course evaluations were positive with median ratings of 4/5 (WB) and 5/5 (F2F). The F2F program received significantly more positive evaluations than the WB program ( p < 0.05), particularly with regard to quality of feedback. Conclusion: WB and F2F simulation are effective education strategies with both programs demonstrating positive learning outcomes. WB programs increase ease of access to training whilst F2F enable the development of tactile hands on skills and teamwork. A combined blended learning education strategy is recommended to enhance competence and patient safety. Highlights: 130 hospital nurses completed parallel patient safety simulation training programs. Both web-based and face-to-face programs improved knowledge, competence and confidence. Patient safety training using a 2-phase blended learning model is recommended.